Associations Between Emotion Regulation Strategies and Anxiety in Lithuanian Medical Students (Baltic Journal of Sport and Health Sciences, 2022)
Background. Appropriate emotion regulation is crucial for medical students to properly prepare for the practical part of their career. Emotion dysregulation, however, is associated with maladaptive emotion regulation strategies, which in turn often causes higher levels of anxiety. This could lead to difficulties concerning the studying process and preparation for the future career. This research is conducted due to the lack of previous studies.Methods. Medical students of Lithuanian University of Health Sciences participated in an online survey. There were a total of 98 female and 18 male students, mean participant age M = 21,6 (SD = 2,21). The survey consisted of 3 questionnaires – Cognitive Emotion Regulation Questionnaire – Short Form (CERQ-SF), GAD-7 and sociodemographic questions. Scales were used to assess emotion regulation strategies and subjective anxiety levels.Results. Female students experience higher levels of anxiety compared to their male counterparts. High levels of anxiety are associated with year 2–6 students; 1st year students are the only ones experiencing low levels of anxiety. However, it is worth mentioning that no statistical significance groups was found in those groups. Results suggest a weak negative correlation between adaptive ER strategies and anxiety, with a moderate positive correlation between maladaptive ER strategies and anxiety. No statistical significance was found between genders, years of study or age concerning the use of ER strategies.Conclusion. Our findings suggest weak negative correlation between adaptive ER strategies and anxiety; moderate positive correlation between maladaptive ER strategies and anxiety was also found.Keywords: medical students, emotion regulation, anxiety.